2006
DOI: 10.1063/1.2162545
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional tunneling Hamiltonian treatment of the microwave spectrum of 2-methylmalonaldehyde

Abstract: The molecule 2-methylmalonaldehyde (2-MMA) exists in the gas phase as a six-membered hydrogen-bonded ring [HO-CH=C(CH(3))-CH=O] and exhibits two large-amplitude motions, an intramolecular hydrogen transfer and a methyl torsion. The former motion is interesting because the transfer of the hydrogen atom from the hydroxyl to the carbonyl group induces a tautomerization in the ring, i.e., HO-CH=C(CH(3))-CH=O-->O=CH-C(CH(3))=CH-OH, which then triggers a 60 degrees internal rotation of the methyl group attached to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(87 citation statements)
references
References 15 publications
3
83
1
Order By: Relevance
“…In addition, the Fourier-transform microwave (FTMW) measurements present a 20-fold improvement in measurement precision, together with a 5-fold improvement given by the millimeter wave measurements. We have also shown that the formalism employed in [2] is capable of fitting these new higher precision measurements to nearly experimental accuracy. This allowed us: (i) to confirm the validity of discarding a few lines from Sanders' tables, (ii) to verify the stability of the molecular constants when more data were added, (iii) to confirm a surprising anomaly in the internal rotation splitting for the normal and singly deuterated species, and (iv) to confirm the validity of the two-dimensional tunneling model for hydrogen transfer and internal rotation to the 10 kHz accuracy level.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In addition, the Fourier-transform microwave (FTMW) measurements present a 20-fold improvement in measurement precision, together with a 5-fold improvement given by the millimeter wave measurements. We have also shown that the formalism employed in [2] is capable of fitting these new higher precision measurements to nearly experimental accuracy. This allowed us: (i) to confirm the validity of discarding a few lines from Sanders' tables, (ii) to verify the stability of the molecular constants when more data were added, (iii) to confirm a surprising anomaly in the internal rotation splitting for the normal and singly deuterated species, and (iv) to confirm the validity of the two-dimensional tunneling model for hydrogen transfer and internal rotation to the 10 kHz accuracy level.…”
Section: Introductionmentioning
confidence: 78%
“…Sanders [1] presented the first microwave measurements on this system, discussed the basic theoretical concepts necessary to understand the rotational spectrum of a molecule with these two large-amplitude motions, and derived a number of molecular parameters from his spectrum. Much later, two of the present authors showed [2] that Sanders' data could be fit with much greater precision using a high-barrier tunneling formalism originally developed for methylamine. The reader is referred to these two papers for further introductory material and background concerning this problem.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…From this, the complete nuclear permutation-inversion (CNPI) group has been developed, which has its origins in the work of LonguetHiggins [10] and Hougen. [11] In the recent past, PI group theory has been successfully applied to a broad variety of complex nonrigid molecules, such as the water dimer (H 2 O) 2 (see also Section 3), [12,13] the methanol dimer (CH 3 OH) 2 , [14] 2-methylmalonaldehyde, [15,16] the dimer CH 3 FÀCHF 3 , [4] acetaldehyde CH 3 COH, [17,18] and the benzene dimer (C 6 H 6 ) 2 , [19] to mention just some to give an impression of its broad applicability. In a recent article, Hougen summarized strategies for advanced applications of PI groups to the microwave spectra of molecules with large-amplitude motions.…”
Section: Introductionmentioning
confidence: 99%